Keeping participants on board: increasing uptake by automated respondent reminders in an Internet-based Chlamydia Screening in the Netherlands - Dokkum Nynke FB; Koekenbier Rik H; van den Broek Ingrid VF; van Bergen Jan EAM; Brouwers Elfi EHG; Fennema Johannes SA; Götz Hannelore M; Hoebe Christian JPA; Pars Lydia L; van Ravesteijn Sander M; Op de Coul Eline LM (BMC, 2012)
Abstract Background Effectiveness of Chlamydia screening programs is determined by an adequate level of participation and the capturing of high-risk groups. This study aimed to evaluate the contribution of automated reminders by letter, email and short message service (SMS) on package request and sample return in an Internet-based Chlamydia screening among people aged 16 to 29 years in the Netherlands. Methods Individuals not responding to the invitation letter received a reminder letter after 1 month. Email- and SMS-reminders were sent to persons who did not return their sample. It was examined to what extent reminders enhanced the response rate (% of package requests) and participation rate (% of sample return). Sociodemographic and behavioural correlates of providing a cell phone number and participation after the reminder(s) were studied by logistic regression models. Results Of all respondents (screening round 1: 52,628, round 2: 41,729), 99% provided an email address and 72% a cell phone number. Forty-two percent of all package requests were made after the reminder letter. The proportion of invitees returning a sample increased significantly from 10% to 14% after email/SMS reminders (round 2: from 7% to 10%). Determinants of providing a cell-phone number were younger age (OR in 25-29 year olds versus 16-19 year olds = 0.8, 95%CI 0.8-0.9), non-Dutch (OR in Surinam/Antillean versus Dutch = 1.3, 95%CI 1.2-1.4, Turkish/Moroccan: 1.1, 95%CI 1.0-1.2, Sub Sahara African: 1.5, 95%CI 1.3-1.8, non-Western other 1.1, 95%CI 1.1-1.2), lower educational level (OR in high educational level versus low level = 0.8, 95%CI 0.7-0.9), no condom use during the last contact with a casual partner (OR no condom use versus condom use 1.2, 95%CI 1.1-1.3), younger age at first sexual contact (OR 19 years or older versus younger than 16: 0.7, 95%CI 0.6-0.8). Determinants for requesting a test-package after the reminder letter were male gender (OR female versus male 0.9 95%CI 0.8-0.9), non-Dutch (OR in Surinam/Antillean versus Dutch 1.3, 95%CI 1.2-1.4, Turkish/Moroccan: 1.4, 95%CI 1.3-1.5, Sub Sahara African: 1.4, 95%CI 1.2-1.5, non-Western other: 1.2, 95%CI 1.1-1.2), having a long-term steady partnership (long-term versus short-term.1.2 95%CI 1.1-1.3). Email/SMS reminders seem to have resulted in more men and people aged 25-29 years returning a sample. Conclusions Nearly all respondents (99.5%) were reachable by modern communication media. Response and participation rates increased significantly after the reminders. The reminder letters also seemed to result in reaching more people at risk. Incorporation of automated reminders in Internet-based (Chlamydia) screening programs is strongly recommended.